The location of the chemical bond. Application of long covalent bond theory to the structure of silica - Miller, Stephen A. (Frontiers in Chemistry, 2023)
Oxygen is the most abundant terrestrial element and is found in a variety of materials, but still wanting is a universal theory for the stability and structural organization it confers. Herein, a computational molecular orbital analysis elucidates the structure, stability, and cooperative bonding of alpha-quartz silica (SiO2). Despite geminal oxygen-oxygen distances of 2.61–2.64 Å, silica model complexes exhibit anomalously large O-O bond orders (Mulliken, Wiberg, Mayer) that increase with increasing cluster size—as the silicon-oxygen bond orders decrease. The average O-O bond order in bulk silica computes to 0.47 while that for Si-O computes to 0.64. Thereby, for each silicate tetrahedron, the six O-O bonds employ 52% (5.61 electrons) of the valence electrons, while the four Si-O bonds employ 48% (5.12 electrons), rendering the O-O bond the most abundant bond in the Earth’s crust. The isodesmic deconstruction of silica clusters reveals cooperative O-O bonding with an O-O bond dissociation energy of 4.4 kcal/mol. These unorthodox, long covalent bonds are rationalized by an excess of O 2p – O 2p bonding versus anti-bonding interactions within the valence molecular orbitals of the SiO4 unit (48 vs. 24) and the Si6O6 ring (90 vs. 18). Within quartz silica, oxygen 2p orbitals contort and organize to avoid molecular orbital nodes, inducing the chirality of silica and resulting in Möbius aromatic Si6O6 rings, the most prevalent form of aromaticity on Earth. This long covalent bond theory (LCBT) relocates one-third of Earth’s valence electrons and indicates that non-canonical O-O bonds play a subtle, but crucial role in the structure and stability of Earth’s most abundant material.